Salt dancers - Hegi, Ursula (Simon & Schuster, 1995)
Julia, an unmarried woman who becomes pregnant at 41, decides to have the baby and in preparation travels to Spokane to visit her father whom she rejected for 23 years. Julia wants to make peace with him before starting her own family and the novel follows the peace process.